2019
DOI: 10.1088/1748-9326/aaf938
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic volume is more responsive than hypoxic area to nutrient load reductions in the northern Gulf of Mexico—and it matters to fish and fisheries

Abstract: While impacts of low oxygen on marine organisms have been reviewed from physiological and ecological perspectives, relating broad population-and ecosystem-level effects to the areal extent of hypoxia (dissolved oxygen concentration below 64 μM, or 2 mg l −1 ) has proven difficult. We suggest that hypoxic volume is a more appropriate metric compared to hypoxic area because volume better integrates the effects of hypoxia on ecological processes relevant to many marine taxa. In this paper, we compare the volume-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 66 publications
(39 reference statements)
2
16
0
Order By: Relevance
“…Benchmarking the goal by hypoxic volume rather than aerial extent, as is done for the Chesapeake Bay, may be more relevant to living resource impacts. A more modest 25% nitrogen load reduction would substantially reduce the thickness of the hypoxic layer to a relatively thin layer near the bottom in much of the affected area (Scavia et al, 2019).…”
Section: Northern Gulf Of Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…Benchmarking the goal by hypoxic volume rather than aerial extent, as is done for the Chesapeake Bay, may be more relevant to living resource impacts. A more modest 25% nitrogen load reduction would substantially reduce the thickness of the hypoxic layer to a relatively thin layer near the bottom in much of the affected area (Scavia et al, 2019).…”
Section: Northern Gulf Of Mexicomentioning
confidence: 99%
“…Furthermore, subsequent research using mass balances (Das et al, 2011) and stable isotopes (Wang et al, 2018) demonstrated that inputs of wetland organic carbon could have only a trivial effect on shelf hypoxia. Recent models have also indicated that the hypoxic volume on shelf west of the Atchafalaya would be substantially ameliorated by reductions of riverine nutrient loads (Scavia et al, 2019). While legitimate scientific debates are appropriate and often helpful, the aforementioned criticisms of reliance on nitrogen source abatement cast doubts that slowed Task Force actions at critical intervals.…”
Section: Northern Gulf Of Mexicomentioning
confidence: 99%
“…Finally, as geostatistical estimates of hypoxic volume become more available, the model could be enhanced to probabilistically predict volume, in addition to hypoxic area. Mid-summer cruise data suggest that hypoxic layer thickness varies substantially over time (Obenour et al 2013), and volume may respond more strongly than area to nutrient loading reductions (Scavia et al 2018).…”
Section: Modeling Approach and Future Directionsmentioning
confidence: 99%
“…Previous studies pointed out that hypoxic volume needs to be considered along with the hypoxic area as another metric in model's ability assessments (Fennel et al, 2016;Scavia et al, 2019). The thickness of hypoxia layers was thus estimated here by integrating the thickness of water layers where DO concentration was ≤ 2 mg L -1 starting from the bottom water layer.…”
Section: Hypoxic Thickness Spatial Distributions Of Bottom Do and Temporal Variability Of Hypoxic Areamentioning
confidence: 99%
“…Hypoxic volume in the LaTex Shelf was deemed to be more sensitive to the changes of river nitrogen loads than the hypoxic area and was therefore considered as a more appropriate metric relevant to ecosystem-level effects (Scavia et al, 2019). We estimated the hypoxic volume according to the thickness of hypoxia layers and the sizes of the corresponding grid cells.…”
Section: Factors To Hypoxic Volume Variabilitymentioning
confidence: 99%